ANALISIS KLASIFIKASI STRATEGI KONTEN BUKALAPAK DALAM PENGGUNAAN SOCIAL MEDIA MARKETINGDI TWITTER (Twitter: @bukalapak) - Resza Manzilina Nurin (2020)
Social media is an alternative for brands in attracting new customers, building relationships with customers, and as a place of promotion. One of the social media that brands use in marketing is Twitter. Twitter is one of the most popular and most commonly used social media in Indonesia. The performance of a brand on Twitter social media is inseparable from the presence of content and how the brand must communicate with the audience. The purpose of this study is to categorize the content type strategy used by one of the popular e-commerce sites in Indonesia, Bukalapak, and to examine the effective types of content with involvement on Twitter. In this study, data were processed using preprocessing and unigram modeling methods in making context or keywords based on the results of the largest TF-IDF representing each category to be used as a reference in categorizing Tweets. The results of this study found the results of categorizing, the content of Bukalapak sharing more Promotion content on Twitter for the audience, and the type of Entertaining content that has the most involvement value.